1981
DOI: 10.1210/jcem-52-4-772
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Origin of Androstanediol and Androstanediol Glucuronide in Young and Elderly Men*

Abstract: The in vivo origin of androstanediol (3 alpha diol) and its glucuronide was studied in six young and five elderly men undergoing cardiac catheterization. Constant infusions of [14C]testosterone and [3H]3 alpha diol were given, and blood was obtained from the aorta and hepatic vein in order to measure metabolic clearance, splanchnic extraction, and the possibility of splanchnic production of both 3 alpha diol and its glucuronide. In young elderly men, the concentrations of labeled and unlabeled testosterone, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The data indicates that neither by mass, radioactivity or specific activity is there any evidence for production of DHT by gut, liver, or splanchnic fat from testosterone or any other steroid entering or produced by splanchnic tissue [32,33]. This conclusion is similar to those reached by us for androstanediol [34]. Therefore, we can conclude that these androgen interconversions occur in extrasplanchnic tissues.…”
Section: In Vivo Steroid Dynamicssupporting
confidence: 80%
“…The data indicates that neither by mass, radioactivity or specific activity is there any evidence for production of DHT by gut, liver, or splanchnic fat from testosterone or any other steroid entering or produced by splanchnic tissue [32,33]. This conclusion is similar to those reached by us for androstanediol [34]. Therefore, we can conclude that these androgen interconversions occur in extrasplanchnic tissues.…”
Section: In Vivo Steroid Dynamicssupporting
confidence: 80%
“…Purification of the extracted steroid was by a celite column where 3a-diol and DHT are clearly separated from testosterone and other C-19 ketosteroids. 3a-diol glucuronide was also measured as previously described (16). Additional characteristics of the assay include: precision 9%, nonspecific blank 6±3 pg, and recovery 86%.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of studies we have demonstrated that DHT and 3a-diol in plasma originates from peripheral conversion of secreted precursors (testosterone and androstenedione) (13,14). Our most recent studies suggest that DHT, 3a-diol and 3a-diol glucuronide in plasma are derived in large part from extrasplanchnic metabolism and that >90% of the glucuronide originates from a pool separate from blood 3a-diol (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the assay was 0.01 nmol/ml and 0.15 pmol/ml, respectively; the intra- and interassay coefficients of variation were 14.8 and 16.6%, respectively. 3α-Androstanediol glucuronide was measured by RIA after extraction with ether and serum hydrolysis with 300 units of β-glucuronidase, following a modified procedure of the technique originally described by Marimoto et al [18]. The intra- and interassay coefficients of variation were 4.6 and 6.8%, respectively.…”
Section: Methodsmentioning
confidence: 99%